Wednesdays in Mississippi : proper ladies working for radical change, Freedom Summer 1964 - Harwell, Debbie Z. (University Press of Mississippi, 2014)
When you think about civil rights activists, do you picture middle-aged, middle-class northern women in white gloves and tidy dresses meeting for coffee with their southern counterparts? This book tells the story of a group of women who did exactly that. As the civil rights movement reached a fevered pitch during Freedom Summer, Wednesdays in Mississippi (WIMS) brought interfaith, interracial teams of northern women to Jackson, Mississippi, to meet with southern women to challenge injustice and open lines of communication where others had failed.